1997
DOI: 10.1016/s0014-5793(97)00371-2
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration that the BchH protein of Rhodobacter capsulatus activates S‐adenosyl‐l‐methionine:magnesium protoporphyrin IX methyltransferase

Abstract: The bchH gene of Rhodobacter capsulatus has been cloned into an expression strain of Eschevichia coli. Following induction of expression of the BchH protein, it was found that the E. coli strain also accumulated porphyrins with the fluorescence properties of protoporphyrin and zinc protoporphyrin. It was also found that the soluble BchH protein increased the activity of Sadenosyl-L-methionine: magnesium protoporphyrin IX methyltransferase, when mixed with membranes of an expression strain of E. coli into which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 41 publications
3
40
0
Order By: Relevance
“…Indeed, a tight channeling of substrate between the magnesium chelatase and the methyltransferase has been suspected for a long time due to the absence of detectable magnesium protoporphyrin intermediates in standard conditions (39). More recently, the physical interaction between CHLM and CHLH has been shown (40,7). During diurnal growth, the magnesium chelatase activity peaks during the transfer from dark to light, whereas the methyltransferase activity maximum follows only a few hours later.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a tight channeling of substrate between the magnesium chelatase and the methyltransferase has been suspected for a long time due to the absence of detectable magnesium protoporphyrin intermediates in standard conditions (39). More recently, the physical interaction between CHLM and CHLH has been shown (40,7). During diurnal growth, the magnesium chelatase activity peaks during the transfer from dark to light, whereas the methyltransferase activity maximum follows only a few hours later.…”
Section: Discussionmentioning
confidence: 99%
“…This porphyrin forms a very tight (possibly covalent) attachment to the H subunit and renders it inactive ; this may be an additional mechanism for the inhibition of Bchl biosynthesis by high oxygen tension and light [69]. Additionally, it has been observed that, in itro, the presence of the H subunit increases the activity of the next enzyme in the pathway, namely the methyltransferase [70]. Interestingly, in whole Rhodobacter cells, it was found that Mgchelatase activity was only measurable if S-adenosylmethionine was included to allow the methyltransferase to operate [12].…”
Section: Regulation Of Bacterial Gene Transcriptionmentioning
confidence: 99%
“…It is proposed that GBP subdivides a small portion of GluTR for ALA synthesis, which is not controlled by the FLU-mediated repression of ALA synthesis in darkness (Czarnecki et al, 2011). Mutual interaction of enzymes, such as the Mg chelatase subunit CHLH and MgP methyltransferase, have been reported to stimulate the enzymatic activities (Hinchigeri et al, 1997;Alawady et al, 2005;Shepherd et al, 2005). Apart from these regulatory interactions of proteins, attachments of chemical-modifying groups and the posttranslational processing of amino acid side chains control the functions of proteins.…”
mentioning
confidence: 99%